2019
DOI: 10.1007/s10714-019-2614-2
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic geometry of a black hole surrounded by perfect fluid in Rastall theory

Abstract: In this paper, we study thermodynamics and thermodynamic geometry of a black hole surrounded by the perfect fluid in Rastall theory. In particular, we calculate the physical quantity like mass, temperature and heat capacity of the system for two different cases. From the resulting heat capacity, we emphasize stability of the system. Following Weinhold, Ruppiner, Quevedo and HPEM formalism, thermodynamic geometry of this black hole in Rastall gravity is also analyzed. We find that the singular points of the cur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 48 publications
1
35
0
Order By: Relevance
“…The plot of the specific heat for different values of ω f , displayed in the left panel of Fig. 3, shows the rich structure of the geometry already noticed in the literature [27][28][29][30][31]. There are positive (stable) and negative (unstable) regions alternating with each other.…”
Section: Thermodynamical Stabilitymentioning
confidence: 58%
See 1 more Smart Citation
“…The plot of the specific heat for different values of ω f , displayed in the left panel of Fig. 3, shows the rich structure of the geometry already noticed in the literature [27][28][29][30][31]. There are positive (stable) and negative (unstable) regions alternating with each other.…”
Section: Thermodynamical Stabilitymentioning
confidence: 58%
“…This constitutes a line-element derived from the solutions studied in [21], the so-called dirty black holes. Studies on its stability [22][23][24][25][26] and some aspects of its thermodynamical behavior have been implemented in the last years [27][28][29][30][31]. However, a detailed description of the causal structure of the spacetime, the late-time behavior of the scalar QNMs, and other aspects related to corrections to the entropy and thermodynamical stability are absent in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to obtain such information about the phase transition of such a charged AdS black hole with a global monopole from Quevedo and HPEM metrics [78]. The phase transition of a black hole surrounded by the perfect fluid in Rastall theory has been studied using the Ruppiner and HPEM metrics, and it has been observed such a phase transition cannot be analyzed using Weinhold and Quevedo metrics [81]. It has been demonstrated that for such a black hole surrounded by the perfect fluid in the Rastall theory, it is possible to extract more information from the HPEM metrics than the Ruppiner metric [81].…”
Section: Jhep10(2021)027mentioning
confidence: 99%
“…Recently, the thermogeometric description using HPEM metric has been provided for the black holes in Rastall gravity [68] and also for the BTZ black holes in the context of massive gravitys rainbow [69].…”
Section: Introductionmentioning
confidence: 99%